Intragranular cracking as a critical barrier for high-voltage usage of layer-structured cathode for lithium-ion batteries - Yan, Pengfei; Zheng, Jianming; Gu, Meng; Xiao, Jie; Zhang, Ji-Guang; Wang, Chong-Min (Nature communications, 2017)
LiNi 1/3 Mn 1/3 Co 1/3 O 2 -layered cathode is often fabricated in the form of secondary particles, consisting of densely packed primary particles. This offers advantages for high energy density and alleviation of cathode side reactions/corrosions, but introduces drawbacks such as intergranular cracking. Here, we report unexpected observations on the nucleation and growth of intragranular cracks in a commercial LiNi 1/3 Mn 1/3 Co 1/3 O 2 cathode by using advanced scanning transmission electron microscopy. We find the formation of the intragranular cracks is directly associated with high-voltage cycling, an electrochemically driven and diffusion-controlled process. The intragranular cracks are noticed to be characteristically initiated from the grain interior, a consequence of a dislocation-based crack incubation mechanism. This observation is in sharp contrast with general theoretical models, predicting the initiation of intragranular cracks from grain boundaries or particle surfaces. Our study emphasizes that maintaining structural stability is the key step towards high-voltage operation of layered-cathode materials. Cycling-induced fracture can limit conditions for stable operation for various lithium-ion electrode materials. Here, the authors characterize fracture in nickel-manganese-cobalt oxide microscopically and provide evidence for dislocation-assisted, intragranular fracture operating above a critical voltage threshold.